ANALISISI EFEKTIVITAS PELAKSANAAN KEBIJAKAN ATAS BARANG KIRIMAN IMPOR PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN C KANTOR POS PASAR BARU - Nurgustriawanti, Eka; Ambarwati, Ambarwati (Jurnal Ilmu Administrasi Publik, 2025)
Customs is one of the agencies that play an important role in increasing economic growth and protecting the people of Indonesia from the entry of dangerous illegal goods. Office of supervision and service of Customs and Excise (KPPBC) type Madya Pabean C Pasar Baru Post Office as the only agency that specifically handles freight services under the Directorate General of Customs and Excise. But in the implementation of the policy of imported goods, still the discovery of violations that occurred resulting in losses to the state. The purpose of this study was to analyze the effectiveness of the implementation of the policy on imported goods at KPPBC Type C Customs Post Office Pasar Baru. The research method used is a qualitative method. The results of this study indicate that the effectiveness in the implementation of policies on imported goods it has been effectively implemented so that 86% of the settlement and action on imported goods becomes state revenue and the achievement of import duty targets with a realization of 122%. However there are several obstacles such as lack of public awareness in policy literacy Minister of finance regulation No.199/PMK.10/2019 imported goods so that there are still many people who commit violations. Efforts made by KPPBC Pasar Baru Post Office is to socialize actively and passively, consult and coordinate with policy makers and  maximize the performance of existing customs officers and officials.